MULTIMEDIA IN LITERACY DEVELOPMENT AT REMOTE ELEMENTARY SCHOOLS IN WEST JAVA (MULTIMEDIA DALAM PENGEMBANGAN LITERASI DI SEKOLAH DASAR TERPENCIL JAWA BARAT) - Hartati, Tatat (Prodi Teknologi Pendidikan, 2016)
Abstract. This research aims to design a multimedia based literacy learning model using PAIKEM (Active, Innovative, Creative, Effective, Fun Learning). This research was located in a remote area in West Java. This research used Research and Development approach. The data was collected through library study, observation, interview, questionnaire and performance assess-ment. The instruments used include RPP, IPKG I, and IPKG II in order to assess the RPP and the learning process. The data analysis was qualitatively descriptive which include: 1) Theoretical analysis about literacy, multimedia and PAIKEM; 2) The analysis of teacher's ability in literacy learning, media and PAIKEM approach; 3) Assessment of teacher's need for media; 4) The devel-opment of learning models which are suitable with teachers' and students' need in remote areas; 5) The analysis of the model developed; 6) Analysis for improvement; 7) Analysis for refinement and dissemination. This research involved two remote schools in Subang regency dan West Ban-dung regency. The results showed that teachers in remote areas of West Java needed training on literacy materials and methods based on PAIKEM and computer use for learning media. The teachers were trained on making learning media using powerpoint and camtasia studio.Keywords: multimedia, literacy, PAIKEM, remote elementary schoolsAbstrak, Penelitian ini bertujuan untuk merancang model pembelajaran literasi ber-basis multimedia dengan menggunakan pendekatan PAIKEM (Pembelajaran Aktif, Inovatif, Kre-atif, Efektif, Menyenangkan). Penelitian ini berlokasi di daerah terpencil Jawa Barat. Pada penelitian ini menggunakan pendekatan, â€œResearch Developmentâ€ . Teknik pengumpulan data melalui kajian pustaka, observasi, wawancara, angket dan penilaian kinerja. Instrumen penelitian terdiri dari RPP dan IPKG I serta IPKG II untuk menilai RPP dan pelaksanaan pembelajaran di sekolah dasar. Analisis data dilakukan secara deskriptif kualitatif mencakup: 1) Analisis teoritis tentang literasi, multimedia dan Pembelajaran Aktif, Kreatif, Inovatif dan Menyenangkan (PAIKEM); 2). Analisis kemampuan guru dalam pembelajaran literasi, media dan pendekatan PAIKEM; 3) Analisis kebutuhan guru (need assessment) tentang media; 4) Pengembangan model pembelajaran sesuai kebutuhan guru dan murid di daerah terpencil;5)Analisis hasil pengembangan model, 6) Analisis untuk perbaikan, 7) Analisis penyempurnaan dan penyebarluasan. Setting yang digunakan adalah dua sekolah terpencil di Kabupaten Subang dan Kabupaten Bandung Barat. Hasil penelitian menunjukkan bahwa guru-guru di daerah terpencil Jawa Barat memerlukan pelati-han materi dan metode literasi berdasarkan PAIKEM dan penggunaan komputer untuk media pem-belajaran. Media computer yang dilatihkan adalah powerpoint dan camtasiastudio.Kata Kunci: multimedia, literasi, PAIKEM, sekolah dasar terpencil